From Good To Great: Total Quality Management In The Housekeeping Department Of A Luxury Resort in Bali - Tayana, Putu Diva Adhi; Indrayani, I Gusti Ayu Putu Wita; Iswarini, Ni Ketut (Journal of Hospitality Accommodation Management (JHAM), 2025)
Total Quality Management (TQM) is a crucial managerial approach within the hospitality industry, essential for achieving consistent operational excellence and optimal, continuous customer satisfaction. This research specifically aims to assess the implementation of TQM within the Housekeeping Department of RB Luxury Hotel. Its primary focus is to deeply understand how key TQM dimensions such as continuous improvement, employee involvement, customer focus, and leadership are truly applied in the daily operations of the housekeeping department. The data analysis method employed is descriptive qualitative, involving in-depth interviews with both room attendants and housekeeping managers to gain perspectives from top and lower management. Additionally, a careful analysis of relevant documents is conducted. Initial findings indicate that TQM implementation in the housekeeping department remains varied; some areas have achieved optimal levels, while others clearly require further enhancement. Therefore, this study also provides practical and measurable recommendations to proactively improve service quality and guest satisfaction on an ongoing basis, ensuring that standards of excellence are consistently maintained for an exceptional and unforgettable stay experience.